2020
DOI: 10.1039/c9gc03152a
|View full text |Cite
|
Sign up to set email alerts
|

Pyrenediones as versatile photocatalysts for oxygenation reactions with in situ generation of hydrogen peroxide under visible light

Abstract: Pyrenediones (PYDs) are efficient photocatalysts for three oxygenation reactions: epoxidation of electron deficient olefins, oxidative hydroxylation of organoborons and oxidation of sulfides via in situ generation of H2O2 from O2 under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Nevertheless, conventional H 2 O 2 production methods like the anthraquinone-based one might mostly be limited by high cost, toxic byproducts, and the complicated yield route . Alternatively, photocatalysis strategies with environmentally friendly, light-driven, and safe semiconductors for H 2 O 2 generation have gathered much attention as the eco-friendly and low-cost strategies. As a matter of fact, unfortunately, high H 2 O 2 yields of photocatalytic strategies have been generally achieved by using noble metals as cocatalysts and/or alcohols as the organic electron donors during the oxygen reduction process, which might encounter with the increased industrial cost and risk of impure products. Hence, it is of great significance to develop a highly efficient semiconductor photocatalyst for H 2 O 2 production without use of noble metal co-catalysts in pure water.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, conventional H 2 O 2 production methods like the anthraquinone-based one might mostly be limited by high cost, toxic byproducts, and the complicated yield route . Alternatively, photocatalysis strategies with environmentally friendly, light-driven, and safe semiconductors for H 2 O 2 generation have gathered much attention as the eco-friendly and low-cost strategies. As a matter of fact, unfortunately, high H 2 O 2 yields of photocatalytic strategies have been generally achieved by using noble metals as cocatalysts and/or alcohols as the organic electron donors during the oxygen reduction process, which might encounter with the increased industrial cost and risk of impure products. Hence, it is of great significance to develop a highly efficient semiconductor photocatalyst for H 2 O 2 production without use of noble metal co-catalysts in pure water.…”
Section: Introductionmentioning
confidence: 99%
“…The result demonstrate that the hydrogen donating ability is decreases from secondary alcohols to primary alcohols. 58 When we optimized the reactions using CPTF@FACC photocatalyst with MeOH, EtOH, and n-butanol solvent, we got the product yield 0%, 27%, and 29% with selectivity 0%, 28%, and 32%, respectively. On the other hand, when we optimized the same reaction by using IPA as a solvent, highest yield (97%) and selectivity (99%) of the product was observed.…”
Section: Characterizationsmentioning
confidence: 99%
“…18 PYD exhibits strong absorption in the visible light region. 19 Moreover, PYD displays excellent excited state oxidizing ability that is ideal for C-H activation. 19 We have previously demonstrated that the generation of H 2 O 2 can be realized via a photocatalytic reaction between PYD and isopropanol, and its capability of in situ oxidizing organic compounds in a mild way.…”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, PYD displays excellent excited state oxidizing ability that is ideal for C-H activation. 19 We have previously demonstrated that the generation of H 2 O 2 can be realized via a photocatalytic reaction between PYD and isopropanol, and its capability of in situ oxidizing organic compounds in a mild way. 19 We herein disclose the photooxidation of a series of C-H partners, including ethers and allylic compounds, by using 1,6-PYD as a photocatalyst under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation